THE ROLE OF SHOPPING ENJOYMENT ON ONLINE IMPULSE BUYING WITH BROWSING AS MEDIATING AND BRAND AWARENESS AS MODERATING - Utami, Wiry; Wati, Linda; Putri, Tyara Dwi; Ismayanti, Rana Surayya (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research examines the role of shopping enjoyment in online impulse buying, with browsing as mediation and brand awareness as moderation. This research uses quantitative methods using Smart-PLS 3.0. The sampling technique used purposive sampling with a total sample of 215 respondents. The research results show that shopping enjoyment has a positive effect on browsing. Shopping enjoyment also has a positive impact on online impulse buying. Browsing has a positive impact on online impulse buying. Browsing mediates the relationship between shopping enjoyment and online impulse buying. Brand awareness moderates the relationship between browsing on online impulse buying.